Recovery following clearing of an upper montane Quercus forest in Costa Rica - Kappelle, Maarten (1993)
Pattems in recovery following clearing of upper montane Quercus forests (2900 - 3000 m alt.) in the Costa Rican Cordillera de Talamanca have been studied and four different successional forest phases (pioneer, ear1y successional, rnid-successional, mature) have been distinguished. Arboreal species richness increases during succession being largest in lhe mid-successional forest phase. Woody Asteraceae dominate lhe ear1y secondary phases, while Araliaceae, Lauraceae and to a lesser extent Myrsinaceae become prominent in later phases including lhe mature stage. Quercus recovers largely, being the dominant genus in mid-successional and mature foresto Young secondary phases are rich in rapid-growing light-demanding canopy species, while more developed multi-layered phases are dominated by a large number of shade-tolerant subcanopy species. In general, secondary succession may lead (within a period of approximately 35 years after clearing and abandonment) to an amoreal recovery ofabout 70 % of the original tree species composition in mature forest.